2004
DOI: 10.3346/jkms.2004.19.5.688
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Levels of VCAM-1, ICAM-1 and E-selectin in Preeclampsia

Abstract: Endothelial dysfunction is thought to be a central pathogenic feature in preeclampsia on the basis of elevated adhesion molecules. The aim of the present study was to compare the levels of soluble vascular cell adhesion molecule-1 (sVCAM-1), intercellular adhesion molecule-1 (sICAM-1) and E-selectin (sE-selectin) in sera of normal and preeclamptic pregnancies. We studied the serum levels of sVCAM-1, sICAM-1 and sE-selectin in normal pregnant women (n=63), mild preeclampsia (n=33) and severe preeclampsia (n=82)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 30 publications
7
64
2
5
Order By: Relevance
“…Moreover, sVCAM-1, sICAM-1, E-selectin, von Willebrand factor (vWf), fibronectin, factor VII antigen and thrombomoduline were found to be significantly increased in severe preeclamptic patients when compared with normal pregnant subjects. 3 The results of these studies support the concept of generalized vascular dysfunction in preeclampsia. In this regard, we thus hypothesized that CECs, as a new marker for endothelial injury, can be increased in preeclampsia and that this new marker can be further used for determining the degree of the disease activity.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, sVCAM-1, sICAM-1, E-selectin, von Willebrand factor (vWf), fibronectin, factor VII antigen and thrombomoduline were found to be significantly increased in severe preeclamptic patients when compared with normal pregnant subjects. 3 The results of these studies support the concept of generalized vascular dysfunction in preeclampsia. In this regard, we thus hypothesized that CECs, as a new marker for endothelial injury, can be increased in preeclampsia and that this new marker can be further used for determining the degree of the disease activity.…”
Section: Discussionsupporting
confidence: 63%
“…Levels of cellular fibronectin, vascular cell adhesion molecule (VCAM)-1, intracellular cell adhesion molecule (ICAM)-1, E-selectin, CD31 and von Willebrand factor have been documented to be elevated in preeclamptic patients even before its clinical manifestation. 3 Additionally, several studies have suggested that women who develop preeclampsia can be at increased risk of cardiovascular complications later in life. 4 An increased number of circulating endothelial cells (CECs) has previously been reported after the onset of various diseases that are associated with endothelial injury, including myocardial infarction, septic shock, sickle cell crisis, antineutrophil cytoplasmic autoantibody (ANCA)-associated small vessel vasculitis, thrombotic thrombocytopenic purpura (TTP), systemic lupus erythematosus and Behçet's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al, indicated that serum levels of E-selectin were significantly higher in both mild and severe PE than a normal pregnancy. However, there were no statistical differences in the levels of E-selectin between mild and severe PE (14). In France, Bretelle et al and Bersinger et al in Switzerland reported similar results in increasing Eselectin in PE (15,16).…”
Section: Resultssupporting
confidence: 61%
“…Increased insulin resistance, a characteristic of gestational diabetes (27), has also been associated with the development of preeclampsia (28)(29)(30). Similarly, abnormal endothelial function with impaired flow mediated dilatation (31)(32)(33) and inflammatory cytokine release as C-reactive protein and E-selectin are reported in both conditions (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%